Cognitive gains as a mechanism of functional capacity improvement in schizophrenia: Results from a multi-site randomized controlled trial. (July 2022) - Flores, Ana T.; Hogarty, Susan S.; Mesholam-Gately, Raquelle I.; Barrio, Concepción; Keshavan, Matcheri S.; Eack, Shaun M.
Abstract: Randomized-controlled trials of Cognitive Enhancement Therapy (CET) reveal its impact on cognitive and functional improvements in schizophrenia and serve as an opportunity for causal claims of potential mediational relationships. In order to examine cognitive gains during CET as a mechanism for improving functional capacity, this secondary analysis included 86 outpatients in the early course of schizophrenia from an 18-month randomized-controlled trial of CET. Functional capacity was measured using the Brief UCSD Performance-Based Skills Assessment (UPSA-B) and cognitive performance by the MATRICS Consensus Cognitive Battery (MCCB) and additional measures of social cognition. Mixed-effects models were used to examine the effects of treatment on the UPSA-B changes and mediation through cognitive improvements. Changes in overall cognition proved to be a significant mediator of CET-related gains in functional capacity at mid-treatment and treatment completion. Exploratory models examining separable cognitive domains further found that improvements in attention, theory of mind, and emotion processing significantly mediated CET effects on functional capacity. This study suggests that CET has potential for improving functional capacity in individuals with schizophrenia, and that cognitive improvements partially mediate this relationship. This evidence can be beneficial for guiding more targeted approaches for rehabilitation in this population.